Sovereignty and the new executive authority - Finkelstein, Claire Oakes; Skerker, Michael (New York, NY : Oxford University Press, 2018)
This volume explores moral and legal issues relating to the concept of sovereignty across four areas. The essays in Part I address foundational questions about the nature of sovereignty and seek to trace the ways in which the traditional concept of sovereignty laid the foundation for the modern conception of executive authority. The essays in Part II examine the tension between the executive's duty to act expeditiously for the public interest and the executive's duty to gain citizens' consent for his or her actions.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 26, 2018).
Keywords: Executive power -- United States; War and emergency powers -- United States; Sovereignty; War and emergency powers; Executive power; Law; Laws of specific jurisdictions & specific areas of law